Prevalence and Pattern of Initial Complications Following Endoscopic Third Ventriculostomy for Hydrocephalus Obstructor - Badar Uddin Ujjan, Shahid Nawaz, Muhammad Sohaib Anwer, Sarah Rehman, Muhammad Kamran, Naseer Hassan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to analyse the complication rate of endoscopic third ventriculostomy for obstructive hydrocephalus. Study Design: Descriptive study Place and Duration: This descriptive study was conducted at Dow International Medical College and Hospital OJHA Campus, Karachi in the period from May, 2022 to October, 2022. Methods: Total 97 male and female patients aged 1-30 presented. Patients had obstructive hydrocephalus were included. With consent, all patients provided age, sex, and BMI. CT and brain MRI were performed. In all reported instances, a third ventriculostomy was done under general anaesthesia after symptoms had become apparent. Two-week follow-up examined post-treatment efficacy and complications. SPSS 26.0 analyzed all data. Results: 66 (68.04%) of the 97 patients were male, while 31(31.96%) were female. The most frequent illness was aqueductal stenosis, which was seen in 64 (65.97%), followed by posterior fossa tumours in 15 (15.5%), blocked VP shunts in 13 (13.4%), and CSF ascites in 5 (5.2%) instances. Frequency of complication was found in 22 (22.7%) cases, most prevalent was CSF leak, followed by meningitis, seizures and bleeding. There were 3 deaths (3.1%) among all cases. Conclusion: In this research, we found that endoscopic third ventriculostomy reduced the risk of complications and death for patients with obstructive hydrocephalus. Keywords: Obstructive Hydrocephalus, Complications, Endoscopic Third Ventriculostomy, Mortality